Predictors of physical and mental health among unemployed people in Greece - Dimitra Latsou; Mary Geitona (Journal of Health and Social Sciences)
Introduction: Unexpected changes such as unemployment are harmful to an individual’s physical and mental health. The aim of this study is to examine the socio-demographic factors affecting the health status of unemployed people in Greece. Methods: A cross-sectional study was conducted in the Manpower Employment Organization entities in the region of Attica, from June 2016 to September 2017. A random sample of 830 unemployed people participated in the study. A self-completion questionnaire was structured including questions on socioeconomic characteristics, physical health based on the Visual Analogue Scale (VAS) and mental health using the CES-D scale. Descriptive and inferential statistics were performed using SPSS 25. Results: The mean age of participants was 35.8 ± 10.3 years, 66.1% were women and 71.8% was short-term unemployed. The mean VAS before unemployment was 85 ±13.6, which decreased to 68.3 ±23.1 during unemployment (P = 0.001) and 55.2% of the sample suffered from depressive symptoms. As far as the sociodemographic characteristics, women (b = -8,011), predisposed individuals to depression (b = -0.610,) and long-term unemployed (b = -1.541) tended to declare poor physical health. In addition, women (b = 1.795), older people (b = 0.179) and long-term unemployed (b = 2,658) were more likely to present predisposition to depression, while parents (b = -4,511) and those who reported good physical health (b = -0.150) did not show depressive symptoms. Discussion and Conclusion: Socio-demographic factors, such as gender, age, existence of children and duration of unemployment appeared to significantly influence unemployed individuals’ health status. Policymakers should continuously support unemployed people through the development of innovative labor and unemployment policies as well as the expansion of their health coverage and access to healthcare in order to improve their overall health status.